PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN T-SHIRT MEREK GT MAN PADA KONSUMEN PT RICKY JAYA SAKTI BANJARMASIN - Sylvia, Rika; Afriana, Rizki Amalia; Yanti, Masitah Putri (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The aim of this research is to determine the influence of product quality on purchasing decisions for GT Man brand T-shirts. The type of research used was quantitative descriptive with a sample of 50 people. The data analysis technique uses multiple linear regression analysis. via the SPSS version 26 program. The results of this research show that product quality (performance, reliability, features, durability, suitability and design) partially has a significant effect on the decision to purchase GT Man T-shirts, namely performance obtained by the value Tcount > Ttable (1.722 > 1.681), reliability Tcount > Ttable (2.776 > 1.681), features obtained Tcount > Ttable (2.181 > 1.681), durability obtained Tcount > Ttable (1.823 > 1.681), suitability obtained Tcount > Ttable (2.239 > 1.681), and design The value obtained is Tcount > Ttable (2.953 > 1.681). Simultaneously, product quality (performance, reliability, features, durability, suitability and design) has a significant influence on the decision to purchase GT Man T-shirts with a value of Fcount > Ftable (10.237 > 2.31).